Florida Beekeeping Management Calendar - James D. Ellis; Mary C. Bammer; William H. Kern Jr. (EDIS)
Climate, plant communities, and timing of floral resources differ significantly across Florida, which means that management of European honey bee colonies in Florida differs as well. This 8-page fact sheet written by James D. Ellis, Mary C. Bammer, and William H. Kern and published by Department of Entomology and Nematology outlines a management calendar created for Florida beekeepers. It is specific to region (north, central, and south Florida) and month and includes recommendations for major management considerations like when to treat for parasites or pathogens and when to feed colonies or harvest honey. This management calendar, while not exhaustive, is a valuable reference or starting point for honey bee colony management in Florida. http://edis.ifas.ufl.edu/in848